2018
DOI: 10.3892/ijmm.2018.3429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silencing the DUSP1 gene using lentiviral vector-mediated siRNA on the release of proinflammatory cytokines through regulation of the MAPK signaling pathway in mice with acute pancreatitis

Abstract: The present study investigated the effects of dual specificity phosphatase 1 (DUSP1) gene silencing using lentiviral vector-mediated small interfering (si)RNA on the release of proinflammatory cytokines through the regulation of the mitogen‑activated protein kinase (MAPK) signaling pathway in mice with acute pancreatitis (AP). Two siRNA‑DUSP1 sequences and one scramble siRNA sequence were designed, and the expression of DUSP1 was detected using western blot analysis to screen for the one with a higher interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Furthermore, the M1 phenotype exacerbates neurotoxicity, whereas the M2 phenotype exerts neuroprotection. , Thus, shifting the microglial polarization from the M1 phenotype toward the M2 phenotype may represent a promising strategy for the treatment of NP. DUSP1 is a key component in regulating anti-inflammatory response . Here, our results confirmed that intra-mPFC injection of LV-DUSP1 attenuated the CCI-induced NP.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, the M1 phenotype exacerbates neurotoxicity, whereas the M2 phenotype exerts neuroprotection. , Thus, shifting the microglial polarization from the M1 phenotype toward the M2 phenotype may represent a promising strategy for the treatment of NP. DUSP1 is a key component in regulating anti-inflammatory response . Here, our results confirmed that intra-mPFC injection of LV-DUSP1 attenuated the CCI-induced NP.…”
Section: Resultssupporting
confidence: 84%
“…KDACs can directly regulate signal transduction pathways. 60 For example, activity of MAPK phosphatase 1 (MKP-1), a phosphatase that regulates signaling converging on JNK, p38, and ERK, 61,62 is dependent upon acetylation. Acetylation of MKP-1 increases its phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the proposal of several mechanisms about the pathophysiological process of AP, none are totally enlightening [10]. Some of the hypotheses include acinar and ductal premature activation of trypsin, leukocyte attraction and activation, recruitment of cytokines, adhesion molecules, and oxygen free radicals, which lead to mitochondrial dysfunction and microcirculatory injury [9,[11][12][13]. Initial AP events take place in the acinar cells [14].…”
Section: Introductionmentioning
confidence: 99%